Biodegradable polymers for the treatment of tuberculosis. Part I. Epidemiology, therapy and treatment methods - Budnicka, M.; Gadomska-Gajadhur, A.; Ruśkowski, P.; Synoradzki, L. (Polimery, 2021)
The paper is an extensive review of the literature concerning the methods of treatment of tuberculosis, present problems and requirements for modern therapy of the disease. The systems for controlled release of active substance (drug delivery systems, DDS) based on various polymer matrices as drug carriers were discussed. The forms of DDS having a potential application in the fight against tuberculosis were briefly presented.